Survey of Blood Groups DEA 1, DEA 4, DEA 5, Dal, and Kai 1/Kai 2 in Different Canine Breeds From a Diagnostic Laboratory in Germany - Ebelt, Anne K.; Fuchs, Sonja; Weber, Corinna; Müller, Elisabeth; Giger, Urs (Frontiers in Veterinary Science, 2020)
More than twelve blood group systems have been described in dogs, but little is known about their distribution frequencies within breed populations. Here we report on an extensive typing survey carried out using available reagents and either established or new clinical kits in purebred dogs from Germany. Leftover anticoagulated blood samples were examined using an immunochromatographic strip method for DEA 1, a gel column technique for Dal and Kai 1/2, and new card agglutination tests for DEA 4 and DEA 5 (which were partially compared with the gel column technique). Monoclonal antibodies were used for DEA 1 and Kai 1/2 typing, and polyclonal antibodies were used for all other types. Among the 206 dogs, 59.2% were DEA 1+, 100% DEA 4+, 9% (Card)/11% (Gel) DEA 5+, 89.3% Dal+, 96.6% Kai 1+, and 2.9% Kai 2+. Erythrocytes from most DEA 1+ dogs bound either strongly or not on the strips, respectively. The agglutination reactions for DEA 5 on the card tests were generally less than those on the gel column. None of the dogs were Kai 1+/2+, and only one was Kai 1-/2-. Dal- dogs were found in several breeds. The blood group pattern DEA 4+, DEA 5-, Dal+, Kai 1+/2- and either DEA 1+ or DEA 1- was found among 80% of the dogs. In this first extensive blood typing survey of purebred dogs from Europe, the proportion of positive and negative blood types were similar to those found in the United States, with considerable breed variation for blood types. The newer typing techniques seem to work well and will be useful to detect and prevent specific blood type incompatibilities in the clinic.